2020
DOI: 10.1002/ejp.1564
|View full text |Cite
|
Sign up to set email alerts
|

Lack of relationship between epidermal denervation by capsaicin and incisional pain behaviours: A laser scanning confocal microscopy study in rats

Abstract: Background Spontaneous pain after surgical incision is a significant problem for most post‐operative patients. Pain management that relies on opioids is hindered by numerous side effects, fuelling interest in non‐opioid alternatives and multimodal approaches. Subcutaneous capsaicin infiltration has shown potential for reducing post‐operative pain, but there are unanswered questions about safety and possible side effects. In adult rats, we characterized the analgesic effects of pre‐operative capsaicin infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 77 publications
3
9
0
Order By: Relevance
“…Previously, we showed that both 1% (200 µl) and 0.05% (200 µl) capsaicin intraplantar injection alleviated spontaneous and thermal pain but not mechanical pain, and did not impact wound healing in a rat postoperative pain model (Kang et al, 2010;Uhelski et al, 2020). In the present study, 50 µl of 0.05% capsaicin intraplantar injection alleviated spontaneous, mechanical, and thermal pain in a mouse postoperative pain model.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previously, we showed that both 1% (200 µl) and 0.05% (200 µl) capsaicin intraplantar injection alleviated spontaneous and thermal pain but not mechanical pain, and did not impact wound healing in a rat postoperative pain model (Kang et al, 2010;Uhelski et al, 2020). In the present study, 50 µl of 0.05% capsaicin intraplantar injection alleviated spontaneous, mechanical, and thermal pain in a mouse postoperative pain model.…”
Section: Discussionsupporting
confidence: 58%
“…Our previous research indicated that intraplantar capsaicin pretreatment before incision alleviates spontaneous and thermal pain due to degeneration of CGRP and IB4/PGP9.5 positive nociceptive nerve fibers in the skin of rats (Kang et al, 2010). In addition, in our experiment with intraplantar capsaicin pretreatment, degeneration of TRPV1-positive primary sensory nerve fibers caused by the capsaicin alleviated spontaneous and thermal pain after plantar incision (Uhelski et al, 2020). Nerve growth factor (Thalakoti, #100) expression level in glabrous skin but not in L4-L6 dorsal root ganglia (DRG) was increased, and increased mRNA levels of insulin-like growth factor-2 (IGF-2) were found using total mRNA sequencing in a rat postoperative pain model (Banik et al, 2005;Tran et al, 2020).…”
Section: Introductionsupporting
confidence: 52%
“…Previous studies have shown that both 1% (200 ml) and 0.05% (200 ml) capsaicin intraplantar injection alleviated spontaneous and thermal pain but not mechanical pain, and did not impact wound healing in a rat incisional pain model (Kang et al, 2010;Tran et al, 2020;Uhelski et al, 2020). The present study used a mouse model plantar incision (Banik et al, 2006;Banik and Brennan, 2009).…”
Section: Discussionmentioning
confidence: 67%
“…Upon initial application, capsaicin evokes pain and hyperalgesia because of the opening of non-selective cation channels located on small diameter neurons expressing TRPV1 receptors. Capsaicin reduced visual analog scores (VAS) in humans and pain-related behaviors in animal models of incisional pain (Hamalainen et al, 2009;Hartrick et al, 2011;Uhelski et al, 2020).The intraplantar capsaicin pretreatment before incision alleviates spontaneous and thermal pain because of degeneration of CGRP and IB4/PGP9.5 positive nociceptive nerve fibers in the skin of rats (Kang et al, 2010). The genomewide transcriptional profiling of dorsal root ganglia (DRG) tissues in a rat model of incisional pain, identified changes in gene expression in the DRG at 1 d after plantar incision, a time point at which pain behaviors were most prominent.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Additionally, our lab and others have reported that intra-plantar infiltration of capsaicin attenuates spontaneous pain behaviors and heat hyperalgesia. 26,27 This phenomenon provides a unique opportunity to identify neural transcriptomes that are specifically induced during incisional pain. For example, incision-induced gene regulatory changes that are sensitive to capsaicin pretreatment are likely involved in the development of pain after incision, whereas those which are insensitive to capsaicin pretreatment are likely involved in processes unrelated to pain.…”
Section: Introductionmentioning
confidence: 99%